Extended Surgical Resections of Advanced Thymoma Masaoka Stages III and IVa Facilitate Outcome - Ried, Michael; Potzger, Tobias; Sziklavari, Zsolt; Diez, Claudius; Neu, Reiner; Schalke, Berthold; Hofmann, Hans-Stefan (The Thoracic and Cardiovascular Surgeon, 2014)
Objective Extended thymoma resections including adjacent structures and pleurectomy/decortication (P/D) with hyperthermic intrathoracic chemotherapy (HITHOC) perfusion were performed in a multidisciplinary treatment regime.Patients and Methods Between July 2000 and February 2012, 22 patients with Masaoka stage III (n = 9; 41%) and Masaoka stage IVa (n = 13; 59%) thymic tumors were included.Results Mean age was 55 years (25–84 years) and 50% (11 out of 22) of patients were female. World Health Organization histological classification was as follows: B2 (n = 15), A (n = 1), B1 (n = 1), B3 (n = 2), and thymic carcinoma (C; n = 3). Radical thymectomy and partial resection of the mediastinal pleura and pericardium were performed. Of the 13, 9 patients with pleural involvement (stage IVa) received radical P/D followed by HITHOC (cisplatin). Macroscopic complete resection (R0/R1) was achieved in 19 (86%) patients. All patients received multimodality treatment depending on tumor stage, histology, and completeness of resection. Thirty-day mortality was 0% and three (13.6%) patients needed operative revision. Recurrence of thymoma was documented in five (22.7%) patients (stage III, n = 1; stage IVa, n = 4). Mean disease-free interval of patients with complete resection (n = 14 out of 22) was 30.2 months. After a mean follow-up of 29 months, 18 out of the 22 (82%) patients are alive. After P/D and HITHOC, 89% (8 out of 9 patients) are alive (current median survival is 25 months) without recurrence.Conclusions Extended surgical resection of advanced thymic tumors infiltrating adjacent structures (stage III) or with pleural metastases (stage IVa) is safe and feasible. It provides a low recurrence rate and an acceptable survival. Additional HITHOC in patients with pleural thymoma spread seems to offer a better local tumor control.
Keywords: thymoma; thymic carcinoma; pleurectomy/decortication; hyperthermic intrathoracic chemotherapy